Foreign aid, fiscal optimality and economic growth in Nigeria - Olufemi Saibu; Felix Obioesio (SPOUDAI - Journal of Economics and Business, 2017)
The main thrust of this study has been to provide empirical illuminations to the debate on the effectiveness of foreign aid in driving sustainable growth and development. Using an extended Barro style model of aid-augmented government expenditure and economic growth, an analytical model is derived to explain this nexus for Nigeria. To obtain estimates free from endogeneity bias; the methodology adopted for the estimation and empirical analysis is based on the IV-2SLS approach. The result from this exercise well conforms to the argument that foreign aid is indeed instrumental to the growth process of Nigeria. The result for our second objective also validates the conventional debate that the growth effects of foreign aid is in most cases conditional on some 'good' macroeconomic policy environment. The implication of our findings is that adequate policy framework and institutional improvement can serve as a veritable path through which foreign aid can most contribute to growth in Nigeria.
Keywords: F35; H21; O23; 330; Foreign Aid; Fiscal Optimality; Economic Growth; IV-2SLS